Literasi Keuangan Nasabah terhadap Pemahaman Sistem Pembiayaan Pegadaian Syariah di Indonesia - Shahrin, Attori Alfi; Ar Rozi, Habib Aziz; Lutfi, Mukhtar; K, Amiruddin (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This research aims to analyze the relationship between customer financial literacy and understanding of the financing system implemented at Sharia Pegadaian in Indonesia. Financial literacy, which includes knowledge, skills and attitudes towards financial management, plays an important role in supporting wise financial decision making, especially in the context of Islamic financial services. This study uses library research. The research results show that customers' financial literacy levels still vary, with several main obstacles such as a lack of understanding of sharia contracts and sharia-based financing mechanisms. Statistical analysis shows a significant positive relationship between financial literacy and understanding of the sharia financing system. These findings emphasize the importance of structured educational efforts to increase financial literacy, especially among people who have not been optimally served by formal financial institutions.